Do We Need Radiotherapy in Grade II Ependymoma? - Napieralska, Aleksandra; Majewski, Wojciech; Miszczyk, Leszek (Frontiers in Oncology, 2022)
Purpose/Objectives The debate on whether radiotherapy (RT) is an essential part of primary treatment in patients with grade II ependymoma (G2E) is still ongoing and this study aims to evaluate its role. Materials/Methods A retrospective analysis of all the consecutive patients treated due to G2E in years 1985–2019 was performed. Group consisted of 116 patients with a small predominance of woman (55% vs 45%) and the location of the tumour in the brain (58% vs 42%). All had surgery as the primary treatment with 47% R0 resection. Radical RT was applied in 81 patients. In majority of cases (91%) patients received local irradiation. Results Median follow-up was 65 months and during that time 17 patients died. Five- and 10-year overall survival (OS) of the whole group was 87% and 83%. Radical surgery (R0 vs R1/2) improved OS (p=0.004), but the difference was observed only in patients with brain lesions (p=0.01). Five- and 10-year progression free survival (PFS) was 68% and 51%. Looking at the treatment of recurrence, those who received RT as a part of the treatment of the recurrent tumour had better OS (p=0.048) – 5- and 10- year OS of 85% and 78% vs 66% and 57%. In the multivariate analysis radical surgery (R0 vs R1/2) and the use of RT in the primary treatment improved PFS (p=0.006 and 0.007). Based on the location of the tumour, the positive influence of RT on PFS was observed only in case of patients with brain tumours (p=0.01). Also, comparing R1/2 surgery with R0 resection – the benefit of RT was only observed in R1/2 group (0.02). Conclusions RT in case of patients with G2E is a valuable treatment of the recurrent disease. Patients with brain lesions after non-radical surgery might benefit from the local irradiation in terms of PFS.